Effect Of Nutrient Deficient Media & Environmental Stressors On Microalgal Growth - Ahmad Syazwan b Zainal Ariff, Ahmad Syazwan (Universiti Teknologi Petronas, 2011)
Research on microalgae has been greatly developed as microalgae are one of the new fast solution‟s to many of world‟s problems such biofuel, environmental remediation, aquaculture and hunger. Microalgae are great factory because of their components that can be extracted and converted into many kinds of product. Every single cell of microalgae is a tiny factory which produces certain useful products. A few of the important extracted product are lipid, carbohydrate and protein, and different species of algae produce different composition of this amount. In order to produce valuable products, it is very important to view algae culture under different environmental stressors to maximize algae production. The studies in this project are based on four different species, which are Isochrysis galbana spp., Tetraselmis batan spp., Nannochloropsis spp. and Pavlouva lutheri spp. The optimum number of cells and kinetic growth of 250C, pH 7, and 24 hours normal light intensity are determined. The extractions of lipid from both fresh and dried algae are done. Different environmental stressors are given to Pavlouva lutheri spp (salinity and photoperiod) and the optical density and amount of lipid content are verified.